ANALISIS GANGGUAN BERBAHASA PADA ANAK DI KECAMATAN PAHAE JULU - Monika Sales Sitompul (JURNAL KONFIKS, 2019)
This study originated from cases of language disorders that occur in society in Pahae Julu district. Language is a need to interact, and humans have been blessed with Language Acquisition Device (LAD) or any language by god. However, if when speaking of someone impaired both LAD and language processing part of the brain, then the communication will not be smooth. The language disorders can happen to anyone. The purpose of this study is to reveal some kinds of language disorders, cases of language disorders and to find out the causes of language disorders experienced by the community in Pahae Julu. The method used in this research is descriptive research method type of case studies.